An uncommon presentation of cryptorchidism - Mishra, Ipseet; Mollah, Washim; Dutta, Arup Kumar; Kumar, Rohan (International Surgery Journal, 2019)
Cryptorchidism as a cause of bowel obstruction is very unsuspecting. Bowel obstructions in cases of cryptorchidism, though reported were mostly as a complication of malignant transformation. Only two case reports of cryptorchidism document a non-malignant aetiology for bowel obstruction. This case is of a 16 year old boy referred for pain abdomen and obstipation for last 3 days. He had signs of peritonitis on examination and so, urgent exploratory laparotomy was planned. A loop of jejunum of approx. 30 cm length at a distance of 35 cm from duodeno-jejunal junction was found gangrenous with gubernacular bands around the loop emerging from a left cryptorchid testis. Resection– anastomosis was done along with left orchidectomy. Histopathology revealed an atrophied testis with no malignant changes. This is the first case report of a non-malignant cryptorchid testis as a cause of strangulated intestinal obstruction in literature.